2019
DOI: 10.3390/w11030472
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Different Amounts of Irrigation and Mulch Films on Physiological Indexes and Yield of Drip-Irrigated Maize (Zea mays L.)

Abstract: Exploring the effect of irrigation on biodegradable film-covered drip-irrigated maize is essential for sustainable agricultural development in arid areas. These regions, like Xinjiang in China, are home to suitable irrigation and biodegradable films. Through field trials, four levels of irrigation, and two biodegradable films and one common polyethylene film were set up to study the effects of different treatments on the physiology, growth indicators, and yield of maize. The results showed that the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…, photochemical quenching coefficient (q p ), non-photochemical quenching coefficient (NPQ), actual photochemical efficiency (Y(II)), and apparent electron transport rate (ETR) were calculated. The calculation formula for each fluorescence parameter uses Rohacek's method [16,17]:…”
Section: Fluorescence Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…, photochemical quenching coefficient (q p ), non-photochemical quenching coefficient (NPQ), actual photochemical efficiency (Y(II)), and apparent electron transport rate (ETR) were calculated. The calculation formula for each fluorescence parameter uses Rohacek's method [16,17]:…”
Section: Fluorescence Indexmentioning
confidence: 99%
“…The actual yield after harvest were measured for each treatment. WUE was calculated as described by Qian [17]:…”
Section: Evapotranspirationmentioning
confidence: 99%
“…Detecting soil moisture conservation benefits of mulches can be difficult given confounding influences of crop and weed growth, precipitation, and irrigation. Nonetheless, in all studies reviewed here, soil moisture beneath BDMs was equal to or greater than in PEM [31][32][33][34][35][36][37][38][39][40]).…”
Section: Soil Moisturementioning
confidence: 99%
“…These polymers can be quickly decomposed and used by microorganisms in nature, and the final degradation products are carbon dioxide and water [24,33]. At present, biodegradable film has been used in the production of greenhouse crops [34,35], potato [36][37][38], spring peanut [39], cotton [40][41][42], maize [42][43][44][45], rice [46,47], and winter wheat [48,49]. As a result, it has been found that biodegradable film can reduce soil residual film pollution, as it is able to fulfill the main functions of PFM: heat preservation, moisture conservation, crop growth, and yield promotion [15,50].…”
Section: Introductionmentioning
confidence: 99%